Body mass index in the populations of the eastern Adriatic Coast from antiquity to the Modern Period (Archaeologia Adriatica, 2023)
Body mass index in archaeological populations is a good indicator of the nutritional load of the organism. It can suggest the quality of life and health of a certain population, or it can be used for comparing populations. Bone remains from archaeological sites on the eastern coast of the Adriatic, dated to the period from antiquity to the Modern Period, were analyzed in the paper. Although it is a relatively small sample, the results of the research showed a decrease in the quality of life, that is, body mass for males, in the periods of the High and Late Middle Ages, which is in line with previous research into Croatian population. During all periods, females had similar, constant body mass, which can be explained not only by the division of labor and availability of food, but also by hormonal influences and different fat metabolism. Body mass index proved to be a good indicator for supplementing knowledge about the quality of life and health of archaeological populations.
Keywords: body mass index; eastern coast of the Adriatic; antiquity; Middle Ages; Modern Period; quality of life